Rozwiązane

Rozwiąż równanie : 9(x-2)=3(x-2)^2



Odpowiedź :

Myślę że pomogłam i liczę na naj

Zobacz obrazek Justynanauaka
Magda

Odpowiedź:

[tex]9(x-2)=3(x-2)^2\ \ /:3\\\\3(x-2)=(x-2)^2\\\\3x-6=x^2-4x+4\\\\3x-6-x^2+4x-4=0\\\\-x^2+7x-10=0\ \ /\cdot(-1)\\\\x^2-7x+10=0\\\\x^2-2x-5x+10=0\\\\x(x-2)-5(x-2)=0\\\\(x-2)(x-5)=0\\\\x-2=0\ \ \ \ \vee\ \ \ \ x-5=0\\\\x=2\ \ \ \ \ \ \ \ \vee\ \ \ \ x=5[/tex]

[tex]II\ \ spos\'ob\\\\9(x-2)=3(x-2)^2\ \ /:3\\\\3(x-2)=(x-2)^2\\\\3x-6=x^2-4x+4\\\\3x-6-x^2+4x-4=0\\\\-x^2+7x-10=0\ \ /\cdot(-1)\\\\x^2-7x+10=0\\\\a=1\ \ ,\ \ b=-7\ \ ,\ \ c=10\\\\\Delta=b^2-4ac\\\\\Delta=(-7)^2-4\cdot1\cdot10=49-40=9\\\\\sqrt{\Delta}=\sqrt{9}=3\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-3}{2\cdot1}=\frac{7-3}{2}=\frac{4}{2}=2\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+3}{2}=\frac{7+3}{2}=\frac{10}{2}=5[/tex]